Analisis Kualitas Daya Sebagai Indikator Keandalan dan Keselamatan Operasional Sistem Distribusi Listrik pada Gedung Bertingkat - Muhammad Rivel Zebertavio; Priyo Adi Sesotyo; Fahrudin Ahmad (Science and Physics Education Journal (SPEJ), 2026)
Abstract:  This study aims to evaluate power quality and analyze its impact on the reliability of electrical distribution systems in a high-rise building. The study employed a quantitative descriptive method through field measurements using a Power Quality Analyzer PEL 103 Chauvin Arnoux installed on the distribution panels of ten floors. The observed parameters included voltage, voltage unbalance, current unbalance, power factor, and total harmonic distortion of voltage (THDv) and current (THDi). The results indicate that the voltage level (229.18–235.02 V), voltage unbalance (0.31–1.17%), power factor (0.86–0.99), and THDv (<5%) comply with IEC 61000, SNI IEC 61000, Permen ESDM No. 04 of 2009, and IEEE 519-2014/2022 standards. However, current unbalance exceeded the permissible limit of 20% on seven floors, and THDi values on several floors exceeded 15%, indicating the presence of nonlinear loads. It can be concluded that the electrical distribution system of the high-rise building exhibits good voltage stability; however, load balancing among phases and harmonic mitigation measures are necessary to maintain the long-term reliability and safety of the electrical installation.   Keywords: Electrical Distribution, Harmonics, High-Rise Building, Power Factor, Power Quality.